1998
DOI: 10.1128/mcb.18.10.5797
|View full text |Cite
|
Sign up to set email alerts
|

Hypersensitivity of Ku-Deficient Cells toward the DNA Topoisomerase II Inhibitor ICRF-193 Suggests a Novel Role for Ku Antigen during the G2and M Phases of the Cell Cycle

Abstract: Ku antigen is a heterodimer, comprised of 86-and 70-kDa subunits, which binds preferentially to free DNA ends. Ku is associated with a catalytic subunit of 450 kDa in the DNA-dependent protein kinase (DNA-PK), which plays a crucial role in DNA double-strand break (DSB) repair and V(D)J recombination of immunoglobulin and T-cell receptor genes. We now demonstrate that Ku86 (86-kDa subunit)-deficient Chinese hamster cell lines are hypersensitive to ICRF-193, a DNA topoisomerase II inhibitor that does not produce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 68 publications
2
20
0
Order By: Relevance
“…The higher resistance of etoposideinduced block to ca eine alleviation is possibly mechanistically linked to the irreversible nature of this block, as compared to the transient nature of Xray-induced block (Poon et al, 1997a). In etoposidetreated cells, ca eine resistance may be related to the inability of cells to undergo normal chromosome condensation, an event that required the participation of DNA topoisomerase IIa (Munoz et al, 1998). In CDT-arrested cells the nature of this ca eineinsensitive component should be investigated further.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The higher resistance of etoposideinduced block to ca eine alleviation is possibly mechanistically linked to the irreversible nature of this block, as compared to the transient nature of Xray-induced block (Poon et al, 1997a). In etoposidetreated cells, ca eine resistance may be related to the inability of cells to undergo normal chromosome condensation, an event that required the participation of DNA topoisomerase IIa (Munoz et al, 1998). In CDT-arrested cells the nature of this ca eineinsensitive component should be investigated further.…”
Section: Discussionmentioning
confidence: 99%
“…Another ca eine-sensitive checkpoint control speci®cally induced in S phase has also been described: the so-called topoisomerase IIdependent G2 checkpoint (Downes et al, 1994). This checkpoint is activated by inhibitors of topoisomerase II such as ICRF-193, which inhibits chromatid decatenation without damaging DNA (Kaufman and Kies, 1998;Munoz et al, 1998). Like CDT, ICRF-193 does not seem to interfere with cell progression through S phase (Ishida et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Earlier work by Muñ oz et al (47) suggested a novel role for Ku at G 2 /M to explain their observation that Ku86-deficient cells were hypersensitive to ICRF-193. This was, however, based on the assumption that the drug is a pure catalytic inhibitor of topo II.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, cytogenetic analysis of ICRF-193-treated E6-expressing cells demonstrated the presence of improperly condensed, entangled chromatids in metaphase spreads (not shown) as commonly observed in ICRF-193-treated mammalian cells. 15,70,75 Evidently, ICRF-193 reached its nuclear target, topoisomerase II, and blocked chromatid decatenation in the E6-expressing cells at high PDL.…”
Section: G2 Checkpoint Response In Normal Humanmentioning
confidence: 99%
“…73 However, mammalian cells exposed to a lower concentration of ICRF-193 prior to mitosis arrest growth in G2. 14,15,74,75 The fact that caffeine could override ICRF-193-induced, but not IR-induced, G2 delay in the DM87 muntjac cell line suggested that IR and ICRF-193 trigger G2 checkpoint response using different signaling pathways. 15 The studies reported here were designed to characterize genetic requirements for the decatenation checkpoint in human cells and determine whether conditions that lead to inactivation of DNA damage G2 checkpoint function also affect the decatenation checkpoint.…”
Section: Introductionmentioning
confidence: 99%